2000
DOI: 10.1038/sj.bjp.0703722
|View full text |Cite
|
Sign up to set email alerts
|

In vivo modulation of vagal‐identified dorsal medullary neurones by activation of different 5‐Hydroxytryptamine2 receptors in rats

Abstract: 1 In in vivo experiments, DOI (a 5-HT 2 receptor agonist), MK-212 (a 5-HT 2C receptor agonist), and BW-723C86 (a 5-HT 2B receptor agonist) were applied by ionophoresis to neurones in the rat nucleus tractus solitarius (NTS) receiving vagal a erent input. 2 The majority of the putative`monosynaptically' vagal activated cells were inhibited by both MK-212 (4/6) and DOI (2/4), but una ected by . In contrast,`polysynaptically' activated NTS cells were excited by both BW-723C86 (13/19) and DOI (9/10). Inactive`inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
10
0

Year Published

2004
2004
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 35 publications
(31 reference statements)
2
10
0
Order By: Relevance
“…However, it has been shown that AngII can exert both inhibitory and excitatory effects in the brainstem [93, 34], consistent with a distribution of phenotypes that traverses a separatrix. Our recent data suggest that phenotypic diversity in autonomic brainstem regions is highly plastic and is coordinated by anatomical connectivity [25], as found in other studies of neuromodulator response in in vivo [91]. Further, it has been shown that constraints at the gene regulatory level, mediated by particular combinations of transcription factors, coordinate physiological processes [94].…”
Section: Discussionsupporting
confidence: 61%
See 1 more Smart Citation
“…However, it has been shown that AngII can exert both inhibitory and excitatory effects in the brainstem [93, 34], consistent with a distribution of phenotypes that traverses a separatrix. Our recent data suggest that phenotypic diversity in autonomic brainstem regions is highly plastic and is coordinated by anatomical connectivity [25], as found in other studies of neuromodulator response in in vivo [91]. Further, it has been shown that constraints at the gene regulatory level, mediated by particular combinations of transcription factors, coordinate physiological processes [94].…”
Section: Discussionsupporting
confidence: 61%
“…However, despite similar baseline firing rates, different conductance balances led to differential responsiveness to neuromodulation, as observed in experimental studies [8,91,92]. These divergent neuromodulation response profiles were associated with different pairwise molecular correlations, indicating that compensatory interactions support robust phenotypes [31].…”
Section: Discussionmentioning
confidence: 97%
“…Within the ventrolateral medulla, previous studies have demonstrated that these neurons with ascending projections to the hypothalamus receive baroreceptor, cardiopulmonary, and vagal input (Li et al, 1992;Gieroba and Blessing, 1993;Stornetta et al, 1999;Verberne et al, 1999) and stimulation of the A1 area has been reported to increase cell discharge of MnPO-PVN neurons through the likely activation of α 1 -adrenoceptors (Tanaka et al, 1992). Alternatively, neurons of the nucleus tractus solitarius respond to cardiopulmonary and vagal afferent fiber activation (Raybould et al, 1988;McCann and Rogers, 1992;Hines et al, 1994;Sevoz-Couche et al, 2000), and orthodromic stimulation of this region typically produces an increase in MnPO cell discharge (Aradachi et al, 1996). Therefore, cardiopulmonary and/or vagal inputs may alter the excitability of MnPO neurons through mono-or polysynaptic pathways via the nucleus tractus solitarius or ventrolateral medulla.…”
Section: Discussionmentioning
confidence: 99%
“…At present, there is evidence suggesting that 5‐HT 3 ( Jeggo et al ., 2005 ) and 5‐HT 7 ( Kellett et al ., 2004 ), but probably not 5‐HT 1A ( Ramage and Mifflin, 1998 ), receptors in the NTS participate in the reflex pathways controlling cardiovascular reflexes. Furthermore, 5‐HT 2A/B and 5‐HT 2C receptors have also been found to affect NTS neurone activity and have opposing actions, excitation and inhibition, respectively ( Sévoz‐Couche et al ., 2000 ). However, central blockade of 5‐HT 2 receptors does not seem to interfere with cardiovascular ( Bogle et al ., 1990 ) or airway ( Bootle et al ., 1996 , 1998 ) reflexes mediated by the NTS.…”
Section: Introductionmentioning
confidence: 99%